ВЛИЯНИЕ НАБУХАЮЩИХ ГИДРОГЕЛЕЙ НА РОСТ ТОМАТОВ В УСЛОВИЯХ РЕГИОНА ПРИАРАЛЬЯ - Асаматдинов, А.; Кудыяров, О. (SCIENCE and SOCIETY, 2025)
The article discusses swelling polymer hydrogels that have the potential to influence soil permeability, density, structure, texture, evaporation rate, and water infiltration through soil. Analysis of the moisture dynamics shows that throughout the field experiment, a positive stable trend towards an increase in soil moisture and an increase in the reserves of productive moisture was noted in the soil with an increase in the dose of hydrogel.
Keywords: hydrogels; swelling; sand; soil; productivity; tomatoes; polymer; water